2023
DOI: 10.1021/acs.joc.3c00287
|View full text |Cite
|
Sign up to set email alerts
|

Design of Bifunctional Pyclen-Based Lanthanide Luminescent Bioprobes for Targeted Two-Photon Imaging

Abstract: In the past, Lanthanide Luminescent Bioprobes (LLBs) based on pyclen-bearing π-extended picolinate antennas were synthesized and demonstrated well-adapted optical properties for biphotonic microscopy. The objective of this work is to develop a strategy to design bifunctional analogues of the previously studied LLBs presenting an additional reactive chemical group to allow their coupling to biological vectors to reach deep in vivo targeted two-photon bioimaging. Herein, we elaborated a synthetic scheme allowing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Not only responding to diverse environmental stimuli by structural modulation based on a molecular platform but also superior NIR emission, stability, and longer lifetimes enable lanthanide-coordinated compounds ideal for fluorescence lifetime imaging (FLIM) [68,69] . Highly stable and luminescent β-fluorinated Yb 3+ complexes, which exhibited strong NIR luminescence (Ф = 23%) and extended decay lifetimes (249 μs), were suitable for both steady-state and time-resolved FLIM within the NIR range [70] . Interestingly, these complexes showed specific luminescent signals, precisely revealing intracellular lifetime distributions (100-200 μs) as FLIM.…”
Section: Biological Imagingmentioning
confidence: 99%
“…Not only responding to diverse environmental stimuli by structural modulation based on a molecular platform but also superior NIR emission, stability, and longer lifetimes enable lanthanide-coordinated compounds ideal for fluorescence lifetime imaging (FLIM) [68,69] . Highly stable and luminescent β-fluorinated Yb 3+ complexes, which exhibited strong NIR luminescence (Ф = 23%) and extended decay lifetimes (249 μs), were suitable for both steady-state and time-resolved FLIM within the NIR range [70] . Interestingly, these complexes showed specific luminescent signals, precisely revealing intracellular lifetime distributions (100-200 μs) as FLIM.…”
Section: Biological Imagingmentioning
confidence: 99%
“…They are routinely employed in LEDs, medical X-ray computed tomography imaging, anticounterfeiting pigments, and strong permanent magnets for diverse applications like MRI scanners and magnetic levitation trains . Additionally, their outstanding optical properties, intricate energy diagrams, and extended lifetimes, drive the development of luminescent tags for bioanalysis and microscopy. …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, macrocyclic pyclen (3,6,9,15-tetraazabicyclo[9.3.1]­pentadeca-1(15),11,13-triene), featuring a pyridine moiety in its backbone, has garnered significant attention as a promising platform for various applications, including MRI CAs, luminescent complexes, and radiometal chelators. Albelda et al developed a pyclen-based complex exhibiting pH-responsive behavior, as the number of coordinated water molecules varies at different pH values from 1 to 2, which results in a change of relaxivity . Tircso et al reported a pH-sensitive MRI probe, PC2A-EA, which contains an ethylamine moiety that can respond within the biologically relevant pH range .…”
Section: Introductionmentioning
confidence: 99%